Tieša mārketinga loma starptautiskā tūroperatora ,,VIA HANSA TOURS"darbībā - Privaļenkovs, Aleksandrs (Latvijas Universitāte, 2009)
Kopš Latvijas neatkarības atgūšanas nemitīgi aug Latvijā ieceļojošo tūristu skaits, kas radīja pamatu ienākošā tūrisma attīstībai valstī un deva jauno ienākumu avotu Latvijas iekšzemes kopproduktam. Šajā procesā Latvijas tūroperatori pilda ne tikai starpnieka lomu, viņu kompetencē ir Latvijas un Baltijas reģiona tūristisko produktu izstrāde un pārdošana, proti, ceļojumu koordinēšana visā reģionā. Ekonomiskās lejupslīdes un konkurences saasināšanas apstākļos Latvijas tūrisma operatori ir spiesti meklēt jaunas pieejas savas uzņēmējdarbības saglabāšanai un turpmākai attīstībai. Šī darba mērķis ir izanalizēt viena no Latvijā lielākajiem tūroperatoriem – „Via Hansa Tours” – situāciju mūsdienu ienākoša tūrisma tirgū, izvērtēt uzņēmuma mārketinga procesu un dot padomus šī procesa uzlabošanai. Darba gaitā tika noskaidrots, kā dota uzņēmuma mārketinga process ir nepilnīgs. Autors ir izstrādājis rekomendācijas mārketinga procesa uzlabošanai un tiešā mārketinga pielietošanai šī procesa ietvaros.

Since the restoration of Latvian Independence and the fall of „Iron Curtain” the number of travellers visiting Latvia has constantly been growing. This fact has given the basis to the development of the incoming tourism in the country and new sources of incomes for Gross National Product. The role of Latvian tour-operators in this process is not limited to the role of the intermediary, but includes the creation & sales of the tourist products of Latvia and Baltic region, namely the coordination of tours. In the conditions of the economic recession and the competition’s aggravation, Latvian tour-operators are forced to search for the new approaches on how to maintain their entrepreneurship and how to develop it further in future. The goal of this study is to analyze the current situation of one of the biggest Latvian tour-operators „Via Hansa Tours” in the incoming tourism market, to evaluate the company’s marketing process and to create the advices for the improvement of this process. While preparing this study, it has been discovered that there are certain lacks in the marketing process of the company. The author of this study has prepared the recommendations on how to improve the company’s marketing process and on how to use the direct marketing methods in this process.
The role of the direct marketing in the international touroperators ,,Via Hansa Tours" activities
Keywords: Vadībzinātne